The Effect of Affiliate Marketing, Price Discounts and Live Streaming Shopping on The Buying Interest of Wardah Products (Kahf Facial Wash) on The Shopee Marketplace : (Case Study: Students of the Faculty of Economics and Business, Baiturrahmah University) - Suhanda, Mya Yuwanita; Syahputra, Eko (Adpebi Science Series, 2024)
This study aims to analyze how affiliate marketing, price discounts, and live streaming shopping simultaneously andpartially affect the buying interest of Wardah products (Kahf Facial Wash) on the Shopee Marketplace. Based on theresults of the SPSS calculation from the t-test, the Affiliate Marketing variable is calculated > ttable or 6.284 > 1.653and the sig value is 0.000 < 0.05, meaning that H1 is accepted and H0 is rejected. So it can be concluded that AffiliateMarketing has a positive and significant effect on the Interest in Buying Wardah Products (Kahf Facial Wash) on theShopee Marketplace. In the Price Discount variable, the calculation > ttable or 7.151 > 1.653 and the sig value of0.000 < 0.05 means that H2 is accepted and H0 is rejected. So it can be concluded that Price Discount has a positiveand significant effect on the Interest in Buying Wardah Products (Kahf Facial Wash) on the Shopee Marketplace. Inthe Live Streaming Shopping variable, the ttable < count or 1.355 < 1.653 and the sig value is 0.177 > 0.05, meaningthat H3 is rejected and H0 is accepted. So it can be concluded that Live Streaming Shopping does not have a significanteffect on the Interest in Buying Wardah Products (Kahf Facial Wash) on the Shopee Marketplace. The samplingtechnique uses a purposive sampling technique, using the Slovin formula so that a sample of 180 people was obtained.The F test is known to have a value of 152,777 > 2.666 with a significant value of (sig = 0.000 < 0.05). So in thisstudy, the independent variables together affect the dependent variables. The determination coefficient was obtainedwith a result of 0.723 which means that the percentage of influence of affiliate marketing, price discount and livestreaming shopping has an influence on the Interest in Buying Wardah Products (Kahf Facial Wash) on the ShopeeMarketplace in students of the Faculty of Economics and Business, Baiturrahmah University by 72.3%, while theremaining 27.7% is influenced by other variables that were not studied in the study.